I'm just no good at rhyming and other nonsense for mischievous kids and immature grown-ups - Harris, Chris, 1970-; Smith, Lane. (New York : Little, Brown and Co., 2017)
"An illustrated collection of comically irreverent rhyming poems for readers of all ages, ranging in topic from avocados and anacondas to zombies and zebras (dressed like ghosts)."--
Keywords: American poetry -- 21st century; Humorous poetry